Chemical Composition and Biological Activity of Essential Oils from Aloe debrana roots. Issue 3 (3rd May 2020) - Getahun, Tokuma; Sharma, Vinit; Gupta, Neeraj
Abstract: The chemical composition of essential oils (EOs) isolated by hydrodistillation (HD) and simultaneous distillation extraction (SDE) from Aloe debrana roots were determined for the first time by GC/MS analysis. The EOs displayed variations in their chemical constituents together with their concentrations. A total of 14 compounds representing 99.1 % of the EO composition isolated by HD were identified with thymohydroquinone dimethyl ether (47.1 %) as a major constituent. Moreover, thirty-three compounds were identified from SDE extracted EO, which represent 88.8 % of the EO constituents with thymohydroquinone dimethyl ether (39.6 %), thymol (7.7 %), humulene epoxide II (5.8 %), dibutyl phthalate (5.0 %) and carvacrol (4.2 %) as major components. Furthermore, the EOs were assessed for their antioxidant activity using DPPH and H2 O2 scavenging assays; and antibacterial activity against S. aureus and E. coli bacteria. Both the EOs demonstrated appreciable activity against these bacterial strains. The EO of A. debrana roots obtained by SDE demonstrated promising antibacterial activity (8.96±1.20 and 13.29±1.06 mm) against Gram-positive S. aureus bacterium at 0.5 and 1.0 mg/mL concentrations, respectively. This EO also showed promising antioxidant activity with IC50 values of 48.65±1.32 ìg/mL in DPPH; and 51.97±2.14 ìg/mL in H2 O2 . Overall results suggest that EOs of A. debrana may be useful in foods, pharmaceuticals, and other industries. However, SDE was found to be an efficient method of EO extraction to identify several compounds from its roots when compared with HD. Moreover, the method was better in terms of EO extraction yield, antioxidant and antibacterial activities.